2008
DOI: 10.1086/591439
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Halo Mass Function for Precision Cosmology: The Limits of Universality

Abstract: We measure the mass function of dark matter halos in a large set of collisionless cosmological simulations of flat ΛCDM cosmology and investigate its evolution at z 2. Halos are identified as isolated density peaks, and their masses are measured within a series of radii enclosing specific overdensities. We argue that these spherical overdensity masses are more directly linked to cluster observables than masses measured using the friends-of-friends algorithm (FOF), and are therefore preferable for accurate fore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

112
2,539
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,853 publications
(2,661 citation statements)
references
References 65 publications
112
2,539
3
7
Order By: Relevance
“…(A3) provides a good approximation. Fitting the approximation to the mass function proposed by Tinker et al (2008), we found that at z 0.3 (1.0), β1 6.8 (11.3) around a pivot mass of M200 = 5 × 10 14 M /h for the standard ΛCDM cosmology.…”
Section: Appendix A: the Mass Functionmentioning
confidence: 80%
“…(A3) provides a good approximation. Fitting the approximation to the mass function proposed by Tinker et al (2008), we found that at z 0.3 (1.0), β1 6.8 (11.3) around a pivot mass of M200 = 5 × 10 14 M /h for the standard ΛCDM cosmology.…”
Section: Appendix A: the Mass Functionmentioning
confidence: 80%
“…Here δ c is the linear theory overdensity at which a spherically symmetric perturbation would collapse. 16 In detail, Tinker et al (2008) find that f (σ) depends on redshift at the 10-20% level, probably because of the dependence of halo mass profiles on Ω m (z). At overdensities of ∼ 200, the baryon fraction in group and cluster mass halos (M > 10 13 M ⊙ ) is expected to be close to the cosmic mean ratio Ω b /Ω m , but gas pressure, dissipation, and feedback from star formation and AGN can alter this fraction and change baryon density profiles relative to dark matter profiles.…”
Section: Cmb Anisotropies and Large Scale Structurementioning
confidence: 97%
“…To a first approximation, the function f (σ) is universal, and the effects of power spectrum shape, redshift (and thus power spectrum amplitude), and background cosmological model (e.g., Ω m and Ω Λ ) enter only through determining |d ln σ/dM | andρ m . The state-of-the-art numerical investigation is that of Tinker et al (2008), who fit a large number of N-body simulation results with the functional form…”
Section: Cmb Anisotropies and Large Scale Structurementioning
confidence: 99%
See 2 more Smart Citations